2013
DOI: 10.2135/cropsci2012.08.0476
|View full text |Cite
|
Sign up to set email alerts
|

Salt Tolerance of 74 Turfgrass Cultivars in Nutrient Solution Culture

Abstract: Turfgrass may experience significant salt stress due to poor water quality, insufficient leaching, or exposure to environmental contaminants. Establishment of salt‐tolerant turfgrass cultivars is one possible method of mitigating the effects of salts in irrigation water or the soil environment. The objective of this research was to evaluate the relative salt tolerance of cool‐season turfgrasses in a controlled environment using digital image analysis. Six replications of 74 cool‐season turfgrasses were establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 18 publications
2
36
0
Order By: Relevance
“…'Bila'. These results agree with Friell et al (2013) investigations which showed the least salt tolerance of P. pratensis varieties compare to other lawn grasses.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…'Bila'. These results agree with Friell et al (2013) investigations which showed the least salt tolerance of P. pratensis varieties compare to other lawn grasses.…”
Section: Resultssupporting
confidence: 92%
“…Plant response to stress conditions during the germination of seeds does not necessarily correlate with vegetative growth. Literature suggests that in the seedling stage varieties of L. perenne show different tolerance of salinity stress (Hujun et al, 2001;Borowski, 2008 a;Kusvuran et al, 2015) whereas P. pratensis should be pointed as moderately sensitive (Friell et al, 2013). Because of that, screening and breeding cool-season turfgrass varieties that are salttolerant during both seed germination and vegetative growth becomes important (Dai et al, 2009).…”
mentioning
confidence: 99%
“…1) showed salinity levels ranging from <1 to 43 dS m -1 , with levels of 10 dS m -1 or greater for the majority of the park (>80% of the area), which exceeded the tolerance limits for cool-season tall fescue. Although Friell et al (2013) showed that tall fescue can tolerate salinity levels of up to 24 dS m -1 for 2 wk in solution culture, Marcum (1999) reported a general threshold of 7 dS m -1 for tall fescue at which a 50% decrease of growth can be observed. Soil salinity at the Chamizal Park is no longer conducive to a high quality stand of tall fescue.…”
Section: Model Calibration and Geospatial Distribution Of Saturated Pmentioning
confidence: 97%
“…; Friell et al . ). Weeping alkaligrass is a halophyte cool season grass that has a high salinity tolerance when cultivated in sodium‐rich soils or in NaCl‐rich hydroponic cultures (Tarasoff et al .…”
Section: Introductionmentioning
confidence: 97%
“…Weeping alkaligrass (Puccinellia distans (L.) Parl) and tall fescue (Festuca arundinacea Schreb.) are turf-grasses that have been widely reported as salinity tolerant (Alshammary et al 2004;Marcum 2006;Gao et al 2012;Friell et al 2013). Weeping alkaligrass is a halophyte cool season grass that has a high salinity tolerance when cultivated in sodium-rich soils or in NaCl-rich hydroponic cultures (Tarasoff et al 2007).…”
Section: Introductionmentioning
confidence: 99%